2011
DOI: 10.4193/rhino09.113
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin desensitization for ASA triad patients--prospective study of the rhinologist's perspective

Abstract: OBJECTIVES/PROBLEM: To determine the sinonasal effect of aspirin salicylic acid (ASA) desensitization in patients with nasal polyps, asthma and aspirin intolerance (ASA triad). METHODS OF STUDY: Patients with ASA triad were recruited from the outpatient otolaryngology clinic. They underwent a program of ASA desensitization (2005 - 2008) with prospective assessment of subjective and objective responses. Incremental doses of aspirin were given to reach a target of 625 mg twice daily during a period of 3 - 5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…[12] Bearing this in mind, we find it logical that studies that have tested considerably higher ASA doses found significant effects on almost every aspect of the disease. [13][14][15][16] However, taking into account the fact that all studies that assessed daily doses of 300 mg [10,12,17] and most studies that assessed daily doses of 100 mg [9,11] still found significant effects, one would always recommend using these relatively low doses. Table 4 gives an overview of the relevant studies addressing oral ASA desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Bearing this in mind, we find it logical that studies that have tested considerably higher ASA doses found significant effects on almost every aspect of the disease. [13][14][15][16] However, taking into account the fact that all studies that assessed daily doses of 300 mg [10,12,17] and most studies that assessed daily doses of 100 mg [9,11] still found significant effects, one would always recommend using these relatively low doses. Table 4 gives an overview of the relevant studies addressing oral ASA desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylsalicylic acid-Desensitization may provide prevention of CRSwNP relapse of sinus surgery. However, these therapies show - depending on their respective dosage - either relatively low efficacy, [ 10 ] may be rich in side effects [ 11 ] and occasionally even both. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Acetylsalicylic acid-Desensitization may provide prevention of CRSwNP relapse of sinus surgery. However, these therapies show -depending on their respective dosage -either relatively low efficacy, [10] may be rich in side effects [11] and occasionally even both. [12] Another, relatively new approach is the regular systemic application of dupilumab (DUPIXENT®), humanized monoclonal antibodies that target the IL-4 and IL-13 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…ASS-Erhaltungstherapie in der vorliegenden Untersuchung beinhaltete aufgrund des retrospektiven Settings eine Dunkelziffer, Nebenwirkungen der Therapie waren aber häufig und alltagsrelevant. Diese Ergebnisse decken sich mit Ergebnissen der Literatur [ 5 , 11 ]. Hinsichtlich des zukünftigen Stellenwerts der ASS-Desaktivierung in Deutschland verbleibt es, auf die Empfehlung der überarbeiteten S2k-Leitlinie der AWMF zu warten.…”
Section: Diskussionunclassified